Assessment of Ice Cream Product Needs Aligning with Consumer Behavior in Thepleela Community - Masantiah, Chuthaphon; Purahong, Warong; Rattanasiri, Muanpare (Interdisciplinary Academic and Research Journal, 2025)
Background and Aims: Assessing consumer demand for ice cream in the Thepleela community is essential for designing products that align with local preferences. This study integrates knowledge from the Bachelor of Arts in Home Economics program to inform product development and support academic service projects for community enhancement. The research aimed to (1) assess the demand for ice cream products in line with consumer behavior and (2) examine the nutritional value and preference rankings of various flavors. Methodology: The study was conducted in two phases. Phase 1 involved a survey with 71 participants, including service providers and consumers, to assess product demand. Data were analyzed using mean and standard deviation. Phase 2 examined nutritional values and consumer preferences for different flavors among 212 participants. A structured recording form was used, and descriptive statistics were applied based on the time taken for each product to be fully consumed. Results: Cookies and Cream emerged as the most preferred flavor, while the 4-ounce serving size received the highest rating. Cookies and Cream also ranked first in consumption rate, with 163 kilocalories and 14 grams of sugar per serving. Conclusion: Cookies and Cream and Strawberry Sherbet were the top two preferred flavors. These findings suggest that future academic service initiatives in the Thepleela community should prioritize these flavors for ice cream production and distribution.